Effect of bagging materials and time on fruit quality of litchi (Litchi chinensis) cv. Shahi in Nagaland - KUMAR, K AJAY; MAITI, C S; ALILA, PAULINE; SARKAR, A; PATIL, PRAKASH (The Indian Journal of Agricultural Sciences, 2023)
The present experiment was conducted during 2020–22 at research farm of School of Agriculture Sciences, Nagaland University, Medziphema campus, Nagaland on effect of bagging in quality of litchi fruits cv. Shahi was Experiment conducted by using3 different bagging materials, i.e. Non- woven Polypropylene White (PPW), Polypropylene Pink (PPP), Brown paper Bag (BPB) and control (no bagging) were used to bagged the fruit bunches at three different days after fruit set, viz. 15 DAFS, 25 DAFS and 30 DAFS. Results indicated that PPP bags gave the best result with higher total sugar (15.21%), TSS (21.30 ºB), TSS: acid ratio (50.34) and low incidence of sunburn (3.59%), fruit cracking (1.71%) in comparison to control, whereby, higher values of anthocyanin content (26.11 mg/100 g) and fruit weight (23.12 g) were recorded in BPB. PPP and BPB bagging materials were found to be the best of the treatments to create mean microclimate inside bag to improve fruit colour and other quality parameters. In the case of time of bagging, 15 DAFS was found to give higher performance as compared to 25 DAFS and 30 DAFS with maximum individual TSS content (21.30 ºB), TSS-acid ratio (50.34) and low Sunburn (3.59%) and cracking percentage (1.71%). As such, bagging with PPP at 15 DAFS was found to give the best treatment.